Performing Counter-Hegemonic Common(s) Senses: Rearticulating Democracy, Community and Forests in Puerto Rico - García López, Gustavo A. (2017)
Political ecologists have developed scathing analyses of capitalism’s tendency for enclosure and dispossession of the commons. In this context commons are analyzed as a force to resist neo-liberalism, a main site of conflict over dispossession, and a source of alternatives to capitalism. In this paper we elaborate a view of the commons as the material and symbolic terrain where performative re-articulation of common(s) senses can potentially enact counter-hegemonic socio-ecological configurations. Expressly drawing on the concepts of hegemony, “common-senses” (inspired by Antonio Gramsci) and “performativity” (developed by Judith Butler), we argue that counter-hegemony is performed through everyday practices that rearticulate existing common senses about commons. Commoning is a set of processes/relations enacted to challenge capitalist hegemony and build more just/sustainable societies insofar as it transforms and rearranges common senses in/through praxis. The paper draws on the experience of an anti-mining movement of Casa Pueblo in Puerto Rico, which for the last 35+ years has been developing a project self-described as autogestion. The discussion pays special attention to Casa Pueblo’s praxis and discourses to investigate how they rearticulate common senses with regard to nature, community and democracy, as well as their implications for counter-hegemonic politics.